Demographic Profile and Upper Gastrointestinal Endoscopic Findings among Children with Gastrointestinal Symptoms (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Upper endoscopy is an essential, safe and sensitive tool for diagnosing pediatric gastrointestinal issues. In Bangladesh, the practice of pediatric endoscopy remain rudimentary due to lackoftrained pediatricendoscopist. There is limited study on pediatric upper GI endoscopy in our country. The aim of the study was to find out the indications, common endoscopic findings and immediate post procedure complication of UGI endoscopy in children. Materials and methods: This is a retrospective study, the medical records of all patients whose age is under 18 years and who underwent upper GI endoscopy in last 2 years were included. Results: Among the total of 150 children (Age